The School for Scandal (London : Published July 18, 1786 by S. W. Fores, N 3 Piccadilly, 1943)
"The reduction of the Prince of Wales's establishment at Carlton House is represented as the auction scene in The School for Scandal (iv. 1) ..." (Source: George)
This record contains unverified data from George.
Catalogue of Political and Personal Satires preserved in the Department of Prints and Drawings in the British Museum / by Mary Dorothy George
Forms part of: British Cartoon Prints Collection (Library of Congress).
Keywords: Cartoons (Commentary) -- British -- 1780-1790.; Engravings -- 1780-1790.